Achieving the Millennium Development Goals for Health and Nutrition in Bangladesh: Key Issues and Interventions - An Introduction (Journal of Health, Population and Nutrition, 2009)
Newcomers to Bangladesh tend to consider this to be a small country because of its small geographic size. However, public-health professionals are less focused on the size of the landmass than they are on the size of the population. Geographic and environmental features shown on maps do influence the health of the population; this is especially true in Bangladesh where the density of population is far higher than any other country that is not a city state. This high density of population, along with poverty and the estuarine environment, contributes significantly to health issues for Bangladesh. However, typical maps do not reveal many features needed to understand the health issues of the country. doi:10.3329/jhpn.v26i3.1893 J Health Popul Nutr 2008 Sept:26(3):253-260